Guidewire crossing techniques in coronary chronic total occlusion intervention: A to Z - Debabrata Dash (Indian Heart Journal, 2016)
Percutaneous coronary intervention (PCI) of chronic total occlusion (CTO) poses a management dilemma for the interventional cardiologist. Effective wiring technique is the key to success of PCI in CTO, which requires more patience and skill of the operator. The author herein intends to explore in detail the different wiring strategies such as antegrade approach, dissection and reentry, retrograde and hybrid approach. Hopefully, this review would enhance the understanding of this complex procedure and, consequently, promote safe and effective PCI.